1994
DOI: 10.1021/ac00092a037
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Denuder Method for Sampling Vapor-Phase Nicotine in Mainstream Tobacco Smoke

Abstract: The partition of nicotine between the vapor and the particulate phases of mainstream tobacco smoke leaving the butt of a cigarette has been determined. Greater than 99% of the nicotine was found to be initially associated with the particles using a technique that draws mainstream tobacco smoke through cylindrical denuders coated with oxalic acid. The rate at which nicotine diffuses from undiluted mainstream tobacco smoke was found to be 38 ± 13 times less than the diffusion rate of nicotine vapor.Tobacco smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 4 publications
2
30
0
1
Order By: Relevance
“…It is not possible at this time to distinguish between the two cited possible mechanisms based on the available data. Denuder tube experiments with fresh MS smoke (in the absence of a Cambridge filter pad) have demonstrated that nicotine is primarily in the particulate phase of MS smoke, that is, <1% of nicotine is in the gas phase of MS smoke (21,33,(52)(53)(54)(55). In addition, the Cambridge filter pad is 99.9% efficient for MS smoke particles that are larger than 0.1 :m in diameter (2).…”
Section: Resultsmentioning
confidence: 99%
“…It is not possible at this time to distinguish between the two cited possible mechanisms based on the available data. Denuder tube experiments with fresh MS smoke (in the absence of a Cambridge filter pad) have demonstrated that nicotine is primarily in the particulate phase of MS smoke, that is, <1% of nicotine is in the gas phase of MS smoke (21,33,(52)(53)(54)(55). In addition, the Cambridge filter pad is 99.9% efficient for MS smoke particles that are larger than 0.1 :m in diameter (2).…”
Section: Resultsmentioning
confidence: 99%
“…The PTFE filter (Tokyo Roshi, Tokyo, Japan, T020A047A) was set in the experimental line after the furnace to eliminate the particles generated in gasification. The amounts of nicotine and menthol were expected to slightly exceed the gas amount in the smoke of our samples according to previous research related to nicotine (Lewis et al 1994). Both gasification and collection were carried out for 10 min through the denuders and impinger at 1.05 and 1.65 L/min.…”
Section: Experimental Methods For Particle Loss Ratio and Gas Collectimentioning
confidence: 99%
“…where D is the diffusion coefficient (cm 2 /s), F is the flow volume (cm 3 /s), L (cm) is the denuder length, C 0 is the concentration at the denuder inlet, and C is the concentration at the denuder outlet, d 1 is the outer diameter of the annulus, and d 2 is the inner diameter of the annulus. The diffusion coefficient of nicotine was referred to as 0.065 cm 2 /s (Lewis et al 1994). As the diffusion coefficient of menthol has not been previously reported, 0.066 cm 2 /s (calculated by Graham's law on the basis of nicotine) was used in the calculation.…”
Section: Gas Collection Efficiency Of the Denuders For Menthol And Nimentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been developed by scientists within and outside the tobacco industry for measuring or estimating free-base nicotine delivery in cigarette smoke. These include the measurement of cigarette "smoke pH" as a means to estimate the fraction of free-base nicotine in cigarette smoke [6,7], the use of organic solvents, such as chloroform, to separate extractable (free-base) nicotine from PP smoke [8], the use of bubbler adsorption to trap the volatile (free-base) nicotine from cigarette smoke [9], and the use of denuder tubes to separate vapor phase (free-base) nicotine from PP nicotine [10,11]. Although each of these methods appears to have allowed some degree of relative comparison of free-base nicotine deliveries among brands, the major limitation is that none of these methods is able to provide absolute measurements of free-base nicotine delivery [1,2].…”
Section: Introductionmentioning
confidence: 99%